Degradation of electric vehicle lithium-ion batteries in electricity grid services. (December 2020) - Elliott, Mark; Swan, Lukas G.; Dubarry, Matthieu; Baure, George
Highlights: EV lithium ion cells (NMC+LMO, LFP) were tested for electricity grid services. Capacity degradation and energy efficiency were monitored over 1200 cycles. Half cell and differential voltage techniques identify degradation mechanisms. Loss of lithium inventory was the main contributor of degradation. Cell choice is influenced by degradation and energy efficiency needs of a service. Abstract: Repurposing retired electric vehicle lithium ion batteries into stationary electricity grid storage will increase their utilization and correspondingly reduce their environmental footprint prior to recycling. In this work, we investigated the performance characteristics of leading commercial cell types repurposed into electricity grid services. Two different positive active materials were compared: (1) a lithium nickel manganese cobalt oxide blended with lithium manganese oxide (LiNiMnCoO2 + LiMn2 O4, termed ``NMC+LMO'') and (2) lithium iron phosphate (LiFePO4, termed ``LFP''). The bulk electricity service of energy arbitrage and the ancillary power electricity service of frequency regulation were tested. Performance was evaluated for energy capacity degradation and round-trip energy efficiency throughout cycle life. Half cell testing and electrochemical voltage spectroscopies were used to investigate the origin of degradation. The results gave useful insight into which chemistries are most appropriate for repurposing into which electricity grid service application. It was found that energy arbitrage service degrades energy capacity approximately twice as fast as frequency regulation service. NMC+LMO degrades approximately twice as fast as LFP. The main energy capacity degradation mechanism comes from loss of lithium inventory. We note that inter-cell capacity degradation differences appear to be a function of overall degradation level. Consequently, the battery management system for repurposed applications must have greater ability to manage inter-cell differences than factory electric vehicle systems. NMC+LMO was more energy efficient than LFP (96% vs 94%) and no degradation of energy efficiency was noted over the first 1200 complete cycle equivalents. This indicates that the thermal management systems applied for electric vehicle purposes is sufficient for repurposed applications. The choice of chemistry type thus depends on the service conducted as some services do not demand long life and some are insensitive to the cost of energy inefficiencies.